2018
DOI: 10.1097/md.0000000000009800
|View full text |Cite
|
Sign up to set email alerts
|

Amputation of multiple limbs caused by use of inotropics

Abstract: Rationale:We present 4 cases of symmetrical peripheral gangrene (SPG) associated with use of inotropic agent to elevate blood pressure. SPG is a relatively rare phenomenon characterized by symmetrical distal ischemic damage that leads to gangrene of 2 or more sites in the absence of large blood vessel obstruction, where vasoconstriction rather than thrombosis is implicated as the underlying pathophysiology. We present 4 SPG cases of the multiple limbs amputation, associated with inevitable use of inotropic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…PG development after treatment for sepsis has been reported in many case reports and, while relatively rare, has serious sequelae [11,17,24,25]. Our study findings highlight the risk factors associated with limb amputation among sepsis survivors; however, they require careful interpretation.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…PG development after treatment for sepsis has been reported in many case reports and, while relatively rare, has serious sequelae [11,17,24,25]. Our study findings highlight the risk factors associated with limb amputation among sepsis survivors; however, they require careful interpretation.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, the 0.8% incidence rate of limb amputation among sepsis survivors in our study was not low when compared with that of other diabetic or general populations. Although there have been case reports of limb amputation among sepsis survivors [ 11 , 16 , 17 ], our study was the first to report the incidence of limb amputation for the treatment of PG in sepsis survivors in South Korea.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Jung et al reported four cases, all of them related to septic shock. 13 Once again, no references to DIC or hepatic failure presence were made, and amputation was necessary. Tan et al described a case of distal ischemia in a 42-yearold male after collision with his motorbike.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Multi-limb ischemia, when occurring without the presence of thromboembolic arterial occlusion, is termed symmetric peripheral gangrene (SPG), and often occurs in the presence of disseminated intravascular coagulopathy (DIC), sepsis, or low-flow states. [27][28][29] SPG has been described in pediatric patients on ECMO after cardiac surgery. 28 We performed an extensive literature search of Ovid database with key search terms (hirudotherapy, leech therapy, limb ischemia, children).…”
mentioning
confidence: 99%